Impact of drought stress on vitamin C and anthocyanin content in cultivated lettuces (Lactuca sativa L.) and wild relatives (Lactuca spp.) - Medina-Lozano, Inés; Bertolín, Juan Ramón; Díaz, Aurora (Frontiers in Plant Science, 2024)
Lettuce production and quality could be seriously affected by the increasingly limited water resources. The effect of drought on the content of two antioxidant compounds, vitamin C and anthocyanins, in five cultivated lettuces and two wild relatives was assessed for 2 years.In leaf samples, Lactuca wild species generally had higher content of total vitamin C than the cultivated lettuces. In contrast, the commercial varieties usually contained more total anthocyanins than the wild species.Total vitamin C decreased with the drought stress in all accessions, commercial varieties and lettuce wild relatives, with this tendency being consistent and reproducible across the 2 years. These differences were significant in the case of the green commercial varieties 'Winter Crop' (in 2020/2021) and 'Dolomiti G12' (in 2021/2022) and very significant in the red commercial variety 'Red Sails' (in 2020/2021). However, the only group in which the effect of drought was either significant or very significant both years was the wild species, Lactuca homblei and Lactuca dregeana, and in the latter also in both tissues (leaf and stem) analysed.Water stress resulted in an increase of the total anthocyanin content in the leaves from all the accessions, both red commercial varieties and wild relatives, both years. The most significant enrichment and the only one being either significant or very significant both years, was observed in one of the wild relatives assayed (L. homblei).Stems (L. dregeana) contained more anthocyanins than leaves under control conditions and it was exactly the opposite under drought. Changes in anthocyanins in the two tissues in response to drought stress were in opposite directions, increasing in leaves and decreasing in stems. This could suggest a translocation of anthocyanins as a first quick mechanism to cope with a severe lack of water.In conclusion, anthocyanins (unlike vitamin C) could play a role in the mechanisms deployed by the plant to tolerate drought stress. The wild species with a robust significant enrichment in anthocyanins as a response to drought (L. homblei) is a promising plant material to breed more resilient lettuces.